PERANCANGAN SISTEM INFORMASI PEMBAYARAN SPP BERBASIS WEB MENGGUNAKAN NOTIFIKASI SMS GATEWAY (Studi Kasus : SMP Puspita Tangerang) - Erna Astriyani; Meri Mayang Sari; Herman Herman (UNIVERSITAS RAHARJA, 2020)
SPP payments still often experience obstacles such as data collection and payment information processes that are done manually where recording reports still use a ledger, making work neglected and spending a lot of time and financial staff in searching student data and archiving. In the current technological era, it is necessary to innovate the use of technology in the world of education to assist the administration of school finance so that the data collection and information process of Payments run effectively and efficiently. In this journal will discuss about the design of web-based SPP payment information systems and sms gateways using sms gateway notifications. This design aims to assist the finance department in recording SPP payments and as a means of informing payments to parents / guardians. The research method used is the SDLC type Waterfall method. This application helps the finance department in recording SPP payments and parents / guardians get payment information every month through SMS notifications.